A survey of fertility and sexual health following allogeneic haematopoietic stem cell transplantation in New South Wales, Australia. (21st December 2015) - Dyer, Gemma; Gilroy, Nicole; Bradford, Jennifer; Brice, Lisa; Kabir, Masura; Greenwood, Matt; Larsen, Stephen R.; Moore, John; Hertzberg, Mark; Kwan, John; Brown, Louisa; Hogg, Megan; et al.
Summary: Four hundred and twenty‐one adult allogeneic haematopoietic stem cell transplant (HSCT) survivors participated in a cross‐sectional study to assess sexual dysfunction and infertility post‐transplant. Survey instruments included the Sydney Post‐Blood and Marrow Transplant (BMT) Survey, Functional Assessment of Cancer Treatment (FACT) – BMT, the Depression, Anxiety, Stress Scales (DASS 21), the Chronic Graft‐versus‐Host Disease (cGVHD) Activity Assessment‐ Patient Self Report (Form B), the Lee cGVHD Symptom Scale and The Post‐Traumatic Growth Inventory. Most HSCT survivors reported sexual difficulties (51% of males; 66% of females). Men reported erectile dysfunction (79%) and decreased libido (61·6%) and women reported loss of libido (83%), painful intercourse (73%) and less enjoyment of sex (68%). Women also commonly reported vaginal dryness (73%), vaginal narrowing (34%) and vaginal irritation (26%). Woman had much higher rates of genital cGvHD than men (22% vs. 5%). Age and cGVHD were significantly associated with sexual dysfunction. Few survivors had children following transplant (3·3%). However, for those of reproductive age at HSCT, 22% reported trying to conceive, with 10·3% reporting success. This study is the largest to date exploring sexual function in survivors of allo‐HSCT. This data provides the basis for health service reform to better meet the needs of HSCT survivors, including evidence to support counselling and education both pre‐ and post‐transplant.